High Variability of Insulin Sensitivity in Closely Related Obese Mouse Inbred Strains - Heise, S.; Trost, J.; Arends, D.; Wirth, E. K.; Schäfer, N.; Köhrle, J.; Schürmann, A.; Brockmann, G. A. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Obesity is one of several risk factors for insulin resistance and type 2 diabetes. Here we examined males of 6 obese mouse inbred lines derived from the Berlin Fat Mouse (BFM) outbred population with respect to insulin sensitivity and factors of the metabolic syndrome with focus on the skeletal muscle as a major target of insulin dependent glucose uptake.Males were kept on a rodent standard diet and several approaches were carried out to address insulin sensitivity, adiposity and lipids in the serum. Transcript and protein levels of several genes in the insulin signalling pathway were measured. 2 of the lines, BFMI860-12 and in particular BFMI861-S1, showed a markedly reduced insulin sensitivity already at the age of 20 weeks. BFMI861-S1 mice also displayed elevated liver triglyceride levels as a sign of lipid overload and ectopic fat storage. The analysis of the insulin signalling pathway in skeletal muscle provided evidence for low insulin receptor (INSR) and normal glucose 4 transporter (GLUT4) protein amounts in BFMI861-S1 mice, while BFMI860-12 mice showed increased INSR and very low GLUT4 protein amounts. Interestingly, the sublines BFMI860-S2 and BFMI861-S2, which are highly related to the former 2 lines, respectively, were inconspicuously insulin sensitive. The expected few genetic differences among the BFMI lines facilitate the identification of causal genetic variation. This study identified 2 mouse lines with different impairments of insulin signalling. These lines resemble useful models for studying mechanisms leading to the pathophysiology of the metabolic syndrome, in particular insulin resistance.
Keywords: adiposity; hyperinsulinemia; skeletal muscle; metabolic syndrome